2021
DOI: 10.1038/s41467-020-20870-1
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide association study of serum liver enzymes implicates diverse metabolic and liver pathology

Abstract: Serum liver enzyme concentrations are the most frequently-used laboratory markers of liver disease, a major cause of mortality. We conduct a meta-analysis of genome-wide association studies of liver enzymes from UK BioBank and BioBank Japan. We identified 160 previously-unreported independent alanine aminotransferase, 190 aspartate aminotransferase, and 199 alkaline phosphatase genome-wide significant associations, with some affecting multiple different enzymes. Associated variants implicate genes that demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 49 publications
4
84
0
Order By: Relevance
“…15,22,23 Recent studies identified APOE, TR1B1, and FTO as potential new loci for liver enzymes. 24,25 Our study extends the results of these studies by linking variation at these loci with a clinical diagnosis of NAFLD and identifies LPL as a potential new susceptibility locus for NAFLD. Interestingly, the minor allele (C) at rs13702 associated here with protection against NAFLD has been predicted to disrupt a microRNA recognition element seed site for human microRNA miR-410, resulting in higher LPL expression.…”
Section: Impact Of the 7 Variants On Nafld After Accounting For Obesitysupporting
confidence: 69%
“…15,22,23 Recent studies identified APOE, TR1B1, and FTO as potential new loci for liver enzymes. 24,25 Our study extends the results of these studies by linking variation at these loci with a clinical diagnosis of NAFLD and identifies LPL as a potential new susceptibility locus for NAFLD. Interestingly, the minor allele (C) at rs13702 associated here with protection against NAFLD has been predicted to disrupt a microRNA recognition element seed site for human microRNA miR-410, resulting in higher LPL expression.…”
Section: Impact Of the 7 Variants On Nafld After Accounting For Obesitysupporting
confidence: 69%
“…viral hepatitis, alcoholic liver disease, hemochromatosis), based on previous validation within VA population 21,31 . In this regard, several GWAS studies of liver enzyme levels have been reported, particularly of serum ALT 10,11,16,34,35 , but not all studies systematically excluded other causes of ALT elevation. For example, Pazoki et al recently reported 230 locis related to ALT, of which 52 were also included in our panel of 77 (67.5%) lead cALT loci 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, several GWAS studies of liver enzyme levels have been reported, particularly of serum ALT 10,11,16,34,35 , but not all studies systematically excluded other causes of ALT elevation. For example, Pazoki et al recently reported 230 locis related to ALT, of which 52 were also included in our panel of 77 (67.5%) lead cALT loci 34,35 . While our cALT approach was designed to enhance the specifity of non-invasive NAFLD diagnosis 21,31 , this overlap is not surprising given the high prevalence of NAFLD in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…GWAS of genes and proteins in sirtuin signaling and the four activated networks we identified show a single gene, FABP1, that has been reported to be associated with alanine aminotransferase levels, a marker of liver disease [ 59 ]. Twelve additional genes were associated with lipoprotein-, insulin-, and BMI-related traits.…”
Section: Discussionmentioning
confidence: 99%